2020
DOI: 10.3892/mmr.2020.11171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic biomarkers and drug target prediction for colon cancer according to a competitive endogenous RNA network

Abstract: colorectal cancer is one of the commoner digestive tract malignant tumor types, and its incidence and mortality rate are high. accumulating evidence indicates that long-chain non-coding rnas (lncrnas) and protein-coding rnas interact with each other by competing with the same micro(mi) rna response element (Mres) and serve an important role in the regulation of gene expression in a variety of tumor types. However, the regulatory mechanism and prognostic role of lncrna-mediated competing endogenous (ce)rna netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
3
8
0
Order By: Relevance
“…Summarizing these results, we believe that MEG3 played a role in cancer development while ZEB1-AS1 could act in both carcinogenesis and cancer development. These results were consistent with previous studies ( Fu and Cui, 2017 ; Gong et al, 2017 ; Liu et al, 2019 ; Hu et al, 2020 ; Ni et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
“…Summarizing these results, we believe that MEG3 played a role in cancer development while ZEB1-AS1 could act in both carcinogenesis and cancer development. These results were consistent with previous studies ( Fu and Cui, 2017 ; Gong et al, 2017 ; Liu et al, 2019 ; Hu et al, 2020 ; Ni et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
“…Similarly, NFAT5, which is a target gene of hsa-mir-206 in the ceRNA network, has been shown to regulate multiple tumor processes. For example, NFAT5 can act as a ceRNA regulated by circFOXO3, plays a role in glioblastoma through sponging miR-138-5p and miR-432-5p [31], and may also regulate the progression of colon cancer through the MALAT1/miR1295p/NFAT5 axis [32]. Here, results from our investigation and the GEPIA website both showed that NFAT5 has a strong relationship with CTB-193M12.1 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“… 9 Long non‐coding RNA (lncRNA) metastasis‐associated lung adenocarcinoma transcript‐1 (MALAT1) can act as competitive endogenous RNA (ceRNA) to regulate its downstream target genes via interaction of microRNA response elements (MREs) and microRNAs (miRNAs). 10 Accumulating evidence proves that knockdown of MALAT1 promotes differentiation of macrophages into M1 subtypes in hepatocellular carcinoma. 11 Additionally, MALAT1 shuttled by exosomes from oxidized low‐density lipoprotein‐treated endothelial cells can promote the M2 polarization of macrophages in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%